2017
DOI: 10.1177/1729881417741739
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of leg exoskeleton cycling-actuated wheelchair

Abstract: This article presents a design of novel wheelchair with a leg exoskeleton for locomotion that can be powered by user legs through a cycling action. In addition, the control system is designed with leg-motion assistance for lower limb muscles to perform exercise during wheelchair motion, targeting elderly persons and users with partial hemiplegia. The simulation results characterize the dynamic operation in three possible modes, fully active, fully passive, and user passive-active action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A user-oriented pedal-actuated exoskeletal wheelchair robot for rehabilitation and locomotion that ensures user safety was proposed in [32]. To meet leg muscles exercise requirements, a crank-rock mechanism was affixed on the wheelchair to enable the leg cycling motion when the wheelchair was active.…”
Section: Conceptual Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A user-oriented pedal-actuated exoskeletal wheelchair robot for rehabilitation and locomotion that ensures user safety was proposed in [32]. To meet leg muscles exercise requirements, a crank-rock mechanism was affixed on the wheelchair to enable the leg cycling motion when the wheelchair was active.…”
Section: Conceptual Designmentioning
confidence: 99%
“…The exoskeletons are designed to guide and assist leg motion while maintaining user safety. Previous work proposed a leg exoskeleton cycling-actuated wheelchair robot with a master-slave control to provide locomotion and rehabilitation functions [32,33,34,35,36] using a crank-rocker mechanism. However, experimentation showed that leg exoskeleton motion was difficult to control when the motor was affixed to the rocker [30] because motion passing through the ‘dead point’ of the crank was user-assisted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years Research Institutes around the world have been looking to increase the quality of life of spinal cord injury (SCI) people by the development of different devices like assistive robots, the design of a mechanism for therapies and devices to transport patients between different zones of the hospital or house [1][2][3][4][5][6][7][8]. There are several examples of devices [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them included the conventional knee ankle foot orthosis (KAFOs) and others were assistive devices such as wheelchairs and crutches, along with modern-day lower-body exoskeletons. 2 Despite providing some sort of assistance, generally, these conventional KAFOs could not provide the desired comfort which leads to unnatural motions. Furthermore, conventional assistive devices have also failed to provide complete independence to the users.…”
Section: Introductionmentioning
confidence: 99%